On the Principle of Estoppel in International Disputes—Taking Preah Vihear Temple Case as an Example Introduction - Sheng Luo (Law and Economy, 2022)
The principle of estoppel in public international law is based on the principles of justice, good faith and consistency. It is the product of applying the principle of estoppel in domestic law to the international community by analogy. Under the promotion of the theories of authoritative jurists and international judicial precedents, it has become a general legal principle in international law. This paper will take the Preah Vihear Temple case as an example to illustrate the nature of estoppel from four aspects, namely, the meaning of the statement must be clear and unambiguous; unilateral commitments can also create an estoppel; no objection (lack of protest) or a silence; and the requirement of a reliance.